Strategi Guru dalam Membentuk Karakter Anak di Taman Kanak-Kanak Islam Terpadu Sunnah An-Najah Takengon - Zulfikar, Dede; Rani; Suminah (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
Education is the most important thing for the development of behavior in children. Teacher strategies in learning are really needed in order to solve the problems found in the learning process. The teacher's strategy in forming children's manners plays an important role, strategies are used to achieve success or success in achieving the goals of manners which must be instilled from an early age. Manners education is human goodness, such as humility, simplicity, self-control, good attitude, trustworthiness, and not being jealous, as well as social goodness, such as good words to keep the secret of iffah. The aim of this research is the teacher's strategy in forming children's manners at the IT Sunnah An-Najah Kindergarten. This research uses descriptive type. Techniques for collecting data using observation, interviews and documentation, data analysis are data collection, data presentation and drawing conclusions. The results and conclusions of the research are that the teacher's strategy at Kindergarten IT An-Najah is to practice habituation, observation, cooperation, direct reprimand, advise and evaluate what is presented in an activity on eating and drinking etiquette, etiquette when entering the bathroom, etiquette when leaving the bathroom, Adab Talking, Adab Borrowing, and Adab meeting the teacher.